THE COMPARATIVE ANALYSIS OF THE OWN PULSATIONS OF A SHAFT COUPLED DIRECTLY TO A DIESEL ENGINE IN CASE OF A GENERATOR SET - Carmen Elisabeta RADU; Edward RĂSCHITOR (Fiabilitate şi Durabilitate)
The paper deals with the determination and comparative analysis of the own pulsations in the case of a generator set consisting of diesel engine and generator, taking into account the possibilities of coupling the flywheels in case of torsional vibrations